Kajian Yuridis terhadap Kedudukan Dana Asuransi dari Sudut Pandang Perjanjian Perkawinan. - Sugiri Permana (AHKAM : Jurnal Ilmu Syariah, 2016)
The Judicial Assessment of the Insurance Fund Status in the Perspective of Marriage Covenant. Ideally, if a legal case comes from the same sources of law, the solution must also be the same although examined by different courts. This case happened on the assessment of the insurance fund. In one hand, the religious courts assessed the insurance fund as heritage while the public court considered the insurance fund as absolute rights of individuals. This article examines the legal differences using treaty law approach. To enrich this analysis, the author presents several court decisions concerning the insurance fund.DOI: 10.15408/ajis.v16i2.4448